Learning from Errors: The case of monetary and fiscal policy regimes - Andreas Tryphonides (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
The New Keynesian theory of inflation determination has been under scrutiny due to identification issues, which rather have to do with the mechanism of inflation determination at its core (i.e. Cochrane (2011)). Moreover, similar identification problems arise in the case of fiscal inflation (see for example Leeper and Leith (2016), Leeper and Li (2017) and Leeper and Walker (2012)). This paper makes a positive contribution. We argue that statements about observational equivalence stem from referring to the equilibrium path, while this should not be our primary source of identifying restrictions. Moreover, policy identification (or lack thereof) relies on assumptions on the underlying shock structure, which is unobservable. We instead extract shocks using heterogeneous uncertain restrictions and external datasets, that is, we learn from errors. We are then able to recover deep and policy parameters irrespective of the prevailing equilibrium. We provide time varying evidence on the efficacy of policy in stabilizing the US economy and on the time varying plausibility of Ricardian versus non-Ricardian price determination. Results are work in progress.
Keywords: C11; C13; E62; E63; 330; Monetary and fiscal policy; Price Determination; Identification; Learning from errors